2021
DOI: 10.1111/age.13044
|View full text |Cite
|
Sign up to set email alerts
|

The equine graying with age mutation of the STX17 gene: A copy number study using droplet digital PCR reveals a new pattern

Abstract: Summary The equine graying with age causative mutation in the syntaxin‐17 gene (STX17) has been known for over a decade, but proper genotyping of this variant remains challenging due to its molecular character (4.6‐kb tandem duplication). Precise information on gray mutation status is important for horse breeders and veterinarians, since gray homozygous horses are more prone to developing aggressive melanoma tumors than heterozygotes. Since recent studies have confirmed that droplet digital PCR is a valuable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Due to the presence of two functional MITF transcription factor binding sites, the region is considered a strong melanocyte‐specific enhancer 1 . Although previous studies recognized the causative variant as tandem duplication, 2 our latest investigation using droplet digital PCR (ddPCR) suggests a novel copy number pattern 3 . Since our results proved interesting to equine geneticists, horse breeders, and veterinarians, we decided to confirm whether the proposed model of STX17 intronic region triplication also holds true when we concentrate exclusively on unique sequences of multiplication breakpoints.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Due to the presence of two functional MITF transcription factor binding sites, the region is considered a strong melanocyte‐specific enhancer 1 . Although previous studies recognized the causative variant as tandem duplication, 2 our latest investigation using droplet digital PCR (ddPCR) suggests a novel copy number pattern 3 . Since our results proved interesting to equine geneticists, horse breeders, and veterinarians, we decided to confirm whether the proposed model of STX17 intronic region triplication also holds true when we concentrate exclusively on unique sequences of multiplication breakpoints.…”
Section: Figurementioning
confidence: 99%
“…To estimate the exact copy number of DNA fragments, we used the equine F2 as a single‐copy reference gene 4 . The protocol of the ddPCR reaction and cycling conditions were identical to those in our previous work 3 . For each sample, approximately 20 000 droplets were generated using a QX200 Droplet Generator.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The causal mutation for Grey was originally identified as a 4.6 kb duplication in intron 6 of Syntaxin 17 ( STX17 ) 1 . However, a recent study 5 , based on digital PCR, indicated that the Grey haplotype carries three copies of the duplicated fragment. Horses homozygous for the Grey mutation ( G/G ) are reported to have significantly higher melanoma incidence than heterozygotes ( G/g ) 1 .…”
Section: Introductionmentioning
confidence: 99%